The basics of synchronized swimming and its injuries - Mountjoy, M. (Clinics in Sports Medicine, 1999)
Synchronized swimming is a complex, physically demanding sport. It is a challenging and interesting sport for the sports medicine clinician. There is opportunity for involvement in program development and in the treatment of medical illness and injury. There is also great potential for clinical research in synchronized swimming because of the paucity of published literature. Greater understanding of the competitive structure, training requirements, and common medical presentations facilitate the management of synchronized swimmers.